Fermenters of the World Unite - Fishel, Stefanie (Cuizine, 2018)
This article explores the power of food and fermentation as a situated and material way for women and feminist communities to come together for change and sustenance. Fermentation processes, when understood as a microbial process, can aid in imagining a feminist political project of transformation that begins in the kitchen, and it can be a powerful metaphor for rethinking politics and equality.